Post-injection subcutaneous atrophy. - Cambiaghi, S.; Maffeis, L.; Boneschi, V.; Fagnani, A.M. (European Journal of Pediatric Dermatology, 2012)
No aggressive surgical therapy is usually needed in young patients with post-injection lipoatrophy, due to its benign, self-healing clinical course. Here is reported the case of a 5-year-old girl who developed a severe subcutaneous atrophy with centrifugal extension in the gluteal region at the site of intramuscular injection of lincomycin plus dexamethasone. The lesions regressed almost completely 6 months later.